Synthesis and Crystal Structure of [(2-Substituted-phenylamino)-(2-hydroxy-phenyl)- methyl]-phosphonic acid Diethyl Esters - Nazir, Hasan; Arici, Cengiz; Aydin, Ahmet; Yilmaz, Hamza (Asian Journal of Chemistry, 2010)
Novel derivatives of [(2-substituted phenylamino)(2-hydroxyphenyl)methyl]phosphonic acid diethyl ester were sysnthesized by addition of diethyl phosphonate to corresponding Schiff bases. The structures of these derivatives have been elucidated on the basis of elemental analyses, IR, NMR and single crystal X-ray diffraction. The [(2-chlorophenylamino)(2-hydroxyphenyl)methyl]phosphonic acid diethyl ester, C17H21NO4PCl (3a) crystallize in monoclinic space group P21/a with unit cell dimensions a = 8.0171(12), b = 33.0519(11), c =15.1195(13) Å, b = 99.859(3) V = 3947.2(7) Å3, Z = 4.